VARIOUS TECHNIQUES TO EVALUATE CARBONACEOUS SOURCE ROCKS AS AN UNCONVENTIONAL GAS RESERVOIR - Ahmad, M. (Asian Research Publishing Network, 2019)
Organic geochemical data of 17 outcrops which were collected in underground mines of Jammu regions of Northwest Himalaya, India was obtained from a published research paper (Mani et al., 2014) in order to study the potential of source rock as an unconventional gas reservoir. The data was obtained by using TOC/Rock-Eval pyrolysis and vitrinite reflectance. TOC/Rock-Eval pyrolysis is the most basic technique used in source rock evaluation. This project involved a case study to learn the techniques to evaluate source rock by using data obtained from various techniques. TOC/Rock-Eval pyrolysis data shows that the total organic carbon (TOC W) of Eocene Subathu shales ranged from 2.42 to 30.4. High TOC value showing that Eocene Subathu shales are good quality source rock with high organic content. Besides that, the values of free hydrocarbon in the source rock (S1) and those hydrocarbon generating through thermal cracking (S2) also observed to be high (S1 ranged from 0.1 to 2.66 and S2 ranged from 0.51 to 15.54 mg HC/g rock). In terms of thermal maturity, the value of Tmax obtained from Rock-Eval pyrolysis observed to be high (Tmax> 4500C for all samples) and vitrinite reflectance also showing a high Ro value (Ro>1.5) indicates that Eocene Subathu shales are post-mature source rock and falls at a dry gas stage. According to HI and OI correlation, organic matter in Eocene Subathu shales are showing characteristics of an over-mature gas prone Type III kerogen with fair to excellence gas generating potential. Â© 2006-2019 Asian Research Publishing Network (ARPN). All rights reserved.